2008
DOI: 10.1111/j.1365-2621.2007.01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Roundup Ready™ soybean in Brazilian soy‐derived foods by real‐time PCR

Abstract: A significant increase in the growth of genetically modified organisms has been observed in recent years. As a result of the market introduction of these genetically modified (GM) crops in foods, legislation worldwide was prepared to deal with the question of the use and labelling requirements on GM crops and their derivatives. The aim of this work was to detect and to quantify GM soybean in soy-derived food products sold commercially in Floriano´polis, Brazil, by polymerase chain reaction-based analysis. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Brod et al (2007) analyzed 37 samples of soy products and found 4 samples of soy flour and 15 samples of soy milk powder that were positive for the presence of RR soybean. Brod and Arisi (2008) analyzed 62 samples of texturized soy protein (TSP) and powdered soymilk and found only 2 samples out of 40 that contained more than 1% of RR soybean. Greiner and Konietzny (2008) published data on 100 processed food products containing soy and 100 containing maize that were analyzed every year from 2000 to 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Brod et al (2007) analyzed 37 samples of soy products and found 4 samples of soy flour and 15 samples of soy milk powder that were positive for the presence of RR soybean. Brod and Arisi (2008) analyzed 62 samples of texturized soy protein (TSP) and powdered soymilk and found only 2 samples out of 40 that contained more than 1% of RR soybean. Greiner and Konietzny (2008) published data on 100 processed food products containing soy and 100 containing maize that were analyzed every year from 2000 to 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Brod and Arisi [19] analyzed 62 samples of soy isolates, of which 37 were of textured soy protein (TSP) and 25 were of soybean extract powder. Forty samples were positive for RR but only two contained more than 1% RR soybean.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works, the presence of RR soybean was detected in soy-based products Brod and Arisi, 2008), in meat additives and processed meat products . Soy-based products are used in food worldwide.…”
Section: Introductionmentioning
confidence: 98%